The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1088/0957-4484/21/21/215602
|View full text |Cite
|
Sign up to set email alerts
|

Large-area aligned branched Cu2S nanostructure arrays: room-temperature synthesis and growth mechanism

Abstract: In this work, an effective approach to synthesize large-area Cu(2)S hierarchical nanotree arrays is presented: Cu nanowire arrays synthesized via template-assisted electrodeposition are used as precursors for the self-growth of branched Cu(2)S nanotree arrays by a gas-solid reaction in H(2)S atmosphere at room temperature. The branched Cu(2)S nanotrees with a high aspect ratio are vertically aligned over the Au film surface, forming a nanoscale 'forest'. Electron microscopy studies reveal that the treelike bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
28
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 41 publications
(57 reference statements)
3
28
0
Order By: Relevance
“…The excitation wavelength is 514.5 nm from an Ar ion laser. A strong and sharp band at 472 cm -1 probably originates from the lattice vibration, which is consistent with the results reported for Cu 2 S films [41,42] and Cu 2 S nanotree arrays [43]. …”
Section: Resultssupporting
confidence: 91%
“…The excitation wavelength is 514.5 nm from an Ar ion laser. A strong and sharp band at 472 cm -1 probably originates from the lattice vibration, which is consistent with the results reported for Cu 2 S films [41,42] and Cu 2 S nanotree arrays [43]. …”
Section: Resultssupporting
confidence: 91%
“…The result showed that cooling by water was necessary and very important in the experiment (Figure S3, Supporting Information). If the cooling was not employed or the cooling rate was slow, there would be some corroded films (as shown in Figures S2a and S3, Supporting Information) which should result from the thermal instability of the Cu 2− x S. The obtained nanosheets ( Figure a) were triangular with obvious Raman peak at 471 cm −1 (Figure b), which was consistent with the reported results of Cu 2 S films . The uniform Raman peak intensity mapping at 471 cm −1 showed that the specimen had pure β phase at room temperature (inset of Figure b).…”
supporting
confidence: 86%
“…23 Among these the electrochemical synthesis of nanomaterials and thin lms could be a cost effective technology for the production of photoelectrochemical cell. Lai et al 27 have reported the template-assisted electrochemical synthesis of Cu 2 S nanowires where copper deposition occurred into the pores of an anodic aluminum oxide. The rationale for this is that thin lms modules are expected to be cheaper in manufacture owing to their low materials cost, energy consumption and handling cost.…”
Section: Introductionmentioning
confidence: 99%